Catalogue of artefacts from Malta in the British Museum - Briffa, Josef Mario 1979-; Sagona, Claudia 1956- (Archaeopress Publishing Ltd, 2017)
Ancient finds from the Maltese islands are rare, and those held in the British Museum form an important collection. Represented is a wide cultural range, spanning the Early and Late Neolithic, the Bronze Age, Roman and more recent historic periods
Previously issued in print: 2017. - Includes bibliographical references
Keywords: Malta / Antiquities / Catalogs